Analisis Efektivitas Strategi Pemasaran Digital untuk Meningkatkan Pertumbuhan Bank Syariah di Indonesia - Anisa Meilita; Muhammad Iqbal Fasa (PT. Intelek Cendikiawan Nusantara, 2024)
This study aims to analyze the effectiveness of the digital marketing strategy implemented by Bank Muamalat Indonesia in enhancing growth and competitiveness in the Islamic banking sector. Amid the advancement of digital technology, Islamic banks must adjust their marketing strategies to remain competitive, particularly with the increasing digital financial transactions in Indonesia. The research method used is descriptive qualitative with literature review as the basis of analysis. The findings indicate that Bank Muamalat has successfully integrated various digital technology innovations such as mobile banking applications, social media, and collaborations with fintech platforms to expand market reach and improve customer loyalty. Additionally, segmented marketing strategies through social media and digital promotions have proven effective in attracting the interest of millennials and Gen Z. However, challenges remain in maintaining a balance between technological innovation and compliance with sharia principles. This study concludes that effective digital marketing can enhance Bank Muamalat's growth in the digital era, though continuous evaluation is necessary to face increasing competition.